Caractérisation éthologique de l’émotivité chez le cercopithèque de Brazza (Cercopithecus neglectus) - Helene Meunier; Philippe Bec; Catherine Blois-Heulin (Revue de Primatologie)
The understanding of the functioning of social groups implies knowledge of the individual characteristics. There are several levels of considering the interindividual differences, the most complex corresponding to the study of the temperament dimensions (Budaev, 1997). Our study takes place at this level and is based on a comparative ethological approach of the temperament according to Bates’ definition (1989). We investigated more specifically one of the main features of this one: the emotivity, defined as the predisposition inherited from the autonomous nervous system, allowing to react in a particularly strong and long-lasting way to certain classes of stimuli (Archer 1973). Most of the studies on emotional reactions are based on only one type of test, in which only few kind of behaviours are recorded (Bouissou et al., 1994). But emotivity domain is complex; it includes, among others, both aspects of gregariousness (Kilgour, 1975 ; Jones, 1977, 1987) and neophobia. We conducted this study on a species of non human primates, De Brazza’s monkey (Cercopithecus neglectus), which tends to be very gregarious and reacting a lot to social isolation (Joly 2000). We tested 5 adult individuals coming from two different social groups on two experimental tests: (1) aspects of gregariousness of the emotional reaction were studied using a test of social isolation, in which subjects were observed in their social group, partially isolated from their social group or totally isolated from their social group; (2) neophobic aspects were addressed with a test of reaction to unknown objects during which subjects were partially or totally isolated from their social group. Each test measured a component of the emotional reaction; an individual could be very gregarious and not much neophobic or conversely. Through these two experiments, we also tested the influence of social environment on emotivity, focusing on intra-individual variation according to the degree of social isolation. Thanks to the control situation, i.e. when subjects were tested within their social groups, individual profiles were drawn up, the five tested subjects presenting persistent individual characteristics through the various observation sessions. In partial social isolation, main behavioural changes were found in environmental exploration, locomotion and vocalizations. However, the more the isolation degree increased, the more the individual profiles were divergent and it appeared a behavioural individualization according to the isolation degree. Various behaviours were modified by the test of reaction to novelty whereas they were not by the test of social isolation; those changes are the “real” responses to the novelty, exempted by the influence of the social isolation. We highlighted three types of behavioural responses: (1) an important neophobia characterized by a lot of threatening vocalizations toward the unknown object and very few approaches; (2) less threats and more approaches of the new object and (3) few or no reaction toward the object. Therefore, besides these results, our study raises the importance of paring both experiments on social isolation and reaction to novelty to be able to isolate the specific reaction to the novelty.